Determinasi Kepatuhan Wajib Pajak Orang Pribadi Berdasarkan Kesadaran, Pemahaman Perpajakan, dan Pemahaman Sanksi Pajak: Studi Kasus di KPP Pratama Klaten - Wijayanti, Afifah Arum; Susilowati, Heni (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
Taxes serve as the primary source of state revenue and a crucial component in financing national development through the State Budget (APBN). This study examines the determinants of individual taxpayer compliance within the Klaten Primary Tax Office (KPP) in Central Java, with particular emphasis on the influence of awareness, comprehension of regulations, and understanding of tax sanctions. The research method uses a quantitative associative approach. Primary data were obtained by distributing questionnaires to 100 respondents using a nonprobability sampling technique, using the accidental sampling method. The data was analyzed using multiple linear regression with the help of SPSS software. The results show that awareness, understanding of regulations, and comprehension of tax sanctions have a statistically significant effect on individual taxpayer compliance, both partially and simultaneously. The adjusted R value illustrates the model's ability to explain the data at 64.7%. To improve taxpayer compliance, tax authorities are advised to routinely conduct sustainable and easily accessible tax education programs, enforce tax sanctions consistently and transparently, and be supported by awareness campaigns for taxpayers in fulfilling their responsibilities to the state.